Prevalência de depressão maior e fatores associados à morbidade depressiva em idosos com 75+ anos residentes na comunidade: estudo Pietà - Filipi Leles da Costa Dias (2018)
Introduction: Among the psychiatric conditions that can affect older adults, major depression is the most prevalent. However, data on depressive morbidity among Brazilian elderly are still scarce, especially among the 75+ years-old. Objectives: To evaluate the prevalence of depressive symptomatology and its associations with sociodemographic, clinical and neuropsychiatric factors among the 75+ years-old population of Caeté (MG). Methods: Cross-sectional population-based study carried on between 2007 and 2008. Participants went through clinical, neuropsychiatric and cognitive evaluations. Major depression (MD) was diagnosed through the MINI and clinically significant depressive symptoms (CSDS) diagnosis was based on the GDS-15. Cognitive evaluation comprised the Mini-mental state examination (MMSE), the Brief cognitive battery (BCB) and Pfeffer´s functional activities questionnaire (FAQ). Results: We evaluated 639 individuals (409 women), with 81.4 ± 5.2 years of age and 2.7 ± 2.6 years of schooling. Among the 632 individuals with a complete psychiatric evaluation, 70 (11.1%) were diagnosed with MD and 146 (25.6%) with CSDS. Groups with both MD and CSDS showed lower quality of life levels. MD was independently related to a history of falls/fracture, to a diagnosis of cognitive impairment-no dementia, to the number of regularly used drugs, to the absence of a reading habit and, inversely, to systolic blood pressure. Depression severity was not influenced by sociodemographic variables. Death/suicide ideation showed to be more common among men (p=0.04), while psychomotor disturbance appeared more frequently among women (p=0.04) and among those with ≥ 4 years of education (p=0.039). Compared to non-depressed individuals, those with MD scored lower on total MMSE (p<0.001) and in some of its sub tests: temporal (p<0.01) and spatial orientation (p=0.021), attention/calculation (p=0.019) and language (p=0.04). They also showed poorer results on incidental (p=0.011), immediate (p=0.046) and learning (p=0.039) memory tasks of the figure memory test as well as in 18 category fluency test (p=0.006), the clock-drawing test (p=0.011) and the FAQ (p<0.001). Excluding individuals diagnosed with dementia, 52 of the remainder 457 (11.4%) were diagnosed with MD. Using the 5/6 cut-off score on the GDS-15, 84 (18.4%) subjects were considered depressed (Kappa = 53.8%, p<0.001), which resulted in an area under the ROC curve of 0.908 (p,0.001). The 4/5 cutoff point achieved the best combination of sensitivity (86.5%) and specificity (82.7%) (Youden´s index = 0.692) with a NPV of 0.9802 and a PPV of 0,3819. Conclusions: Our data support the notion that MD is a highly prevalent condition among the 75+ years-old population, is associated to specific sociodemographic and clinical characteristics and is accompanied by cognitive deficits. Although sociodemographic variables had no influence of depression severity, gender and educational level were related to distinct symptomatic profiles. GDS-15 showed good accuracy as a screening tool for depression and the 4/5 cut-off point achieved the best performance in this community-based sample of low-educated 75+ years-old individuals.